Understanding Residential Real Estate in China - Chivakul, Mali (IMF Working Papers; Working Paper ;, 2015)
China's residential real estate sector plays an important role in the economy and has been a key driver of growth. Since 2014 the sector has softened visibly, reflecting overbuilding across many cities. An orderly adjustment of the sector is welcome. The key questions are how severe the adjustment will be and how long it will last. This paper uses various datasets, an analytical framework to estimate demand and supply conditions, and develops a number of scenarios to determine the oversupply both at the national level and by city tiers. It highlights that the adjustment will be a multiyear process with adverse implications for investment and growth. Smaller cities, as well as those in the Northeast region, face more challenging demand-supply dynamics. The key will be to allow the adjustment to take place, while avoiding a too sharp of an economic slowdown.